Tingkat Pengetahuan Mahasiswa Terhadap Penggunaan Obat Analgetik Antipiretik Secara Swamedikasi pad Kampus Kesehatan dan Non Kesehatan di Kota Bengkulu - Rais Khasanah, Heti; Baharyati, Delta; Permata Sari, Tara (Avicenna: Jurnal Ilmiah, 2025)
Background: Self-medication is a common self-medication practice among the public, drugs often used for self-medication are analgesic and antipyretic drugs. Knowledge of the use of these drugs is crucial to ensure safe and effective self-medication and to avoid unwanted side effects. Objective: The study aims to determine the level of student knowledge regarding the use of analgesic and antipyretic drugs by self-medication on Health and Non-Health campuses in Bengkulu City. Method: The study used a descriptive quantitative method using a cross-sectional research design using a questionnaire sheet of 11 questions with a total of 100 Health students and 100 Non-Health students. The sampling technique was accidental sampling. Results: The results show that from the age level of Health students and Non-Health students, respondents aged 19-22 years were more willing to be respondents. The gender of respondents from Health students and Non-Health students showed that female students were more willing to be respondents. Based on the level of knowledge of Health students, the categories were good (74%), sufficient (23%), and less (3%). While the level of knowledge of Non-Health students was good (66%), sufficient (29%), and less (5%). So the Mann Whitney U result has a significant value of 0.038 <0.05, which means there is a significant difference in the level of knowledge between Health students and Non-Health students regarding the use of antipyretic analgesic drugs for self-medication. Conclusion: The level of knowledge of Health students is higher (74%) than that of non-health students (66%).